The Impact of Social Media Marketing and Brand Image on Purchasing Decisions at Babelmart Belitung - Nugroho, Christephen Adi; Wahyono, Seno Aji; Widyaningrum, Santi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Currently, marketing via platforms has become important for companies to reach consumers and build a strong brand image. This research aims to analyze the impact of Social Media Marketing (SMM) and Brand Image (BI) on purchasing decisions at Babelmart Belitung using quantitative methods and collecting data through questionnaires distributed to 160 Babelmart Belitung customers. The results show that Social Media Marketing (SMM) and Brand Image (BI) simultaneously significantly influence purchasing decisions. Social Media Marketing (SMM) increases consumer engagement and interaction, while strong Brand Image (BI) increases trust and loyalty. Partially, Social Media Marketing (SMM) has a positive effect on purchasing decisions, but Brand Image does not. Babelmart Belitung is advised to continue optimizing marketing activities on social media and strengthening Brand Image (BI) to increase sales and customer satisfaction.